Pembaruan Pendidikan Agama Islam di Madrasah - Machsun, Toha (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2017)
Islamic Religious Education in madrasas still tends to be subordinated by Muslims in Indonesia. The implications of this discourse discourse has an impact on the development of human resources that human resources development that has not been effective and efficient, so that Islamic Religious Education in madrasas does not develop professionally. Islamic Education in madrasas does not develop professionally. However, as an institution, madrasah remains optimistic in providing a new breakthrough to formulate a critical to formulate the critical reasoning of Islamic religious education, both vision-mission, curriculum materials, methods and infrastructure, so that Islamic Religious Education still exists. education, so that Islamic Religious Education continues to exist in society by mastering the quality of education and society by mastering the quality of education and updating the education system as a whole